Tightening joints by optimized grinding of mating surfaces - Huseynov, Hasan; Bagirov, S. A. (Allerton Press, 2026)
The tightness of a flat joint is considered, taking account of the finishing of the mating surfaces. The tightness may be improved by adjusting the shape precision, the undulation, and the roughness of the mating surfaces. On that basis, a device is developed for controlling the elastic compression of the system consisting of the machine tool, the attachment, the tool, and the part. In addition, a grinding wheel with abrasive grains of different size is proposed, so as to integrate rough grinding and finishing in a single operation.
Keywords: Joints; Tightness; Surface roughness; Process elements